SCIENTIFIC FUNDAMENTALS OF INTEGRATION AS ONE OF THE TRENDS DEVELOPMENT OF THE MODERN SCHOOL (Pedagogy of Higher and Secondary Education, 2022)
The article has made an attempt to define the scientific grounds of integration, to give a broad online its potential in terms o f the teaching process in modern school
Keywords: 1